Solid state NMR characterization and flammability of styrene-acrylonitrile copolymer montmorillonite nanocomposite - Bourbigot, S.; Vanderhart, D.L.; Gilman, J.W.; Bellayera, S.; Stretz, H.; Paul, D.R.
This work investigates the melt-processing of styrene-acrylonitrile copolymer (SAN)with organo-modified montmorillonite (MMT)clays and the influence of the clay on mechanical properties and on fire performance of SAN. The nanodispersion of MMT is evaluated qualitatively by X-ray diffraction (XRD)and transmission electronic microscopy (TEM), and quantitatively by solid state nuclear magnetic resonance (NMR). SAN/MMT nanocomposites reveal an intermediate morphology, an intercalated structure with some exfoliation and with the presence of small tactoids, whatever the loading in MMT is. The polymer-clay interfacial area is estimated at 0.5 and the degree of homogeneity characterizing the distribution of MMT platelets is about 40
Keywords: SOLID STATE NUCLEAR MAGNETIC RESONANCE; NANOCOMPOSITE; STYRENE-ACRYLONITRILE COPOLYMER